Experiences of mothers of NICU preterm infants in milk management out of the hospital: a qualitative study - Rui Yang; Danqi Chen; Hua Wang; Xinfen Xu (BMC, 2022)
Abstract Background Human milk is important for the health and development of preterm infants. China's neonatal intensive care units (NICUs) have adopted the management system of maternal-infant separation. Human milk received and used by NICUs is managed by the infants' families in the out-of-hospital environment. There is scant publication on mothers' opinions on out-of-hospital human milk management. This study aimed to explore the experiences of Chinese mothers providing their infants in the NICUs with human milk expressed outside of the hospital. Methods Semi-structured interviews were conducted with 23 participants recruited from June 2020 to November 2020, who transported their human milk to the human milk bank of Women's Hospital School of Medicine Zhejiang University during the hospitalization of their preterm infants. This study adopted a qualitative research approach with thematic analysis. Results Three main themes were identified: 1) awareness of human milk management and a willingness to adopt it; 2) lack of standardization regarding expressing, storing, and transporting expressed human milk; and 3) the need for more external support. Theme 2 additionally has three sub-themes: I) differentiation of preparations before human milk expression; II) differentiation of devices for human milk expression; and III) insufficient knowledge and understanding. Conclusions In this study, all participants who received health education showed enthusiasm for participating in out-of-hospital human milk management. However, most participants had questions during the implementation process. Medical staff should provide professional and continuous external support to support mothers in implementing human milk management.